Examining Housing Environments and Health Status of Older Adults with Physical Disabilities in South Korea. Issue 6 (2nd November 2021) - Kim, Miok; Woo, Bongki; Kim, Hyun-Jun; Yi, Eunsil; Hong, Seunghye
ABSTRACT: The present study examined the relationships between housing environments and health and well-being among older adults with physical disabilities in South Korea. Data are from the 2014 National Survey on Persons with Disabilities. We modelled four health and well-being outcomes – perceived stress, depressive symptoms, suicidal ideation, and life satisfaction – by various housing environments among 2, 077 older adults with physical disabilities. The results illustrate that home ownership and perceived house accessibility are associated with health and well-being. Findings indicate that efforts to promote the health of older adults with physical disabilities need to be accompanied by improvements in their housing environment.